2019
DOI: 10.1097/spv.0000000000000524
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Colporrhaphy With and Without Dermal Allograft: A Randomized Control Trial With Long-Term Follow-Up

Abstract: We cannot conclude whether there is a difference in anterior recurrence for anterior colporrhaphy with and without dermal allograft and do not recommend changes in clinical practice based on these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The estimated number of required participants is based on the primary outcome. We estimate that the rate of success defined by combined objective and subjective measures of the anterior colporraphy is about 45% at 1 year, with anatomical success defined with Aa and Ba point of 0 [ 6 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The estimated number of required participants is based on the primary outcome. We estimate that the rate of success defined by combined objective and subjective measures of the anterior colporraphy is about 45% at 1 year, with anatomical success defined with Aa and Ba point of 0 [ 6 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prospective studies have shown anatomical success rates of anterior colporraphy ranging from 42% [ 11 ] to 69% [ 12 ]. Retrospective studies have shown functional success rates between 72.7% [ 5 ] and 78% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kelly et al proposed an anterior colporrhaphy with tissue plication just below the bladder and urethra [6] . The entire assembly was then fixed in the periurethral plane and reattached to the midline.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of our study is the prospective randomised design, Similar published studies on this topic had also presented results with small sample sizes and multiple surgeons. 33,34 Finally, the study is based on the presence or absence of a thin layer of loose connective tissue in the anterior vaginal wall trimming. The nature of this connective tissue, and its role in the pathogenesis and repair of vaginal wall prolapse, is controversial.…”
Section: Strength and Limitationsmentioning
confidence: 99%